Called to civil existence : Mary Wollstonecraft's a vindication of the rights of woman - Steiner, Enit Karafili (Guft va gū ;, 2014)
Mary Wollstonecraft's A Vindication of the Rights of Woman (1792), a continuation of her earlier Vindication of the Rights of Men (1790), was the first feminist treatise to emerge within a broader context of liberationist human rights theory. Rights of Woman remains, however, relevant and instructive. The essays included here show that Wollstonecraft's legacy is still with us today as the balancing act between a society where sexual distinction translates into gender prejudice and a utopian order where sexual difference ceases to be a structuring element of social, economic and political bias.